A conceptual analysis of the public health-architecture nexus within rapidly developing informal urban contexts - Patrick, Sean M.; Hugo, Jan; Sonnendecker, Paul; Shirinde, Joyce (Frontiers in Environmental Science, 2024)
Abstract BACKGROUND: The interactions between people and places can have a significant impact on the well-being of individuals, particularly in warm, arid countries such as South Africa. Coupled to this are the various risks that climate change poses to the development of communities, particularly in informal settlements. Several of these risks include the increasing prevalence of contaminants in water and land, as well as the challenges of managing the effects of climate change. OBJECTIVES: This conceptual analysis aims to highlight the need for a transdisciplinary approach to investigating the interaction between informal urban living spaces, environmental and social determinants of health and further propose a framework that incorporates tools and strategies to improve health and well-being. DISCUSSION: Despite the various advantages of living in an urban environment, many people in informal settlements still lack access to adequate sanitation and water services. This is why it is important that we develop a comprehensive understanding of how these changes can be accommodated in the future. This can be done through the collection of data from the people who live in these communities. A comprehensive understanding of the environmental and social determinants of health, coupled with innovative monitoring systems, would provide a more holistic approach to suggesting a practical strategy for promoting health and well-being in communities while working towards developing safe and sustainable health-promoting living spaces. CONCLUSION: Currently there is a paucity of information regarding access to water, sanitation and health services, coupled with environmental pollution and poor living conditions causing diseases affecting informal communities, furthermore practical and viable changes to address these concerns are similarly lacking. To ensure that healthier built environments are provided for children and adults, transdisciplinary approaches between researchers and collaboration with, communities within informal settlements and with policymakers to promote health advocacy is essential.